ANALYSIS OF THE DEVELOPMENT POTENTIAL OF BABURAI WATERFALL TOURISM OBJECT IN PADANG PARIAMAN REGENCY - Pratama, Aldi Aditio; Osronita; Hary Febrianto; Nina Ismayani; Yudas Sabaggalet; Desi Eka Putri; Andri Yanto (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Baburai Waterfall, located in Padang Pariaman Regency, is one of the tourist attractions with tourism potential; however, in reality, this tourist attraction has not maximized the existing potential. This study aims to (1) describe the tourism potential of Baburai Waterfall in Padang Pariaman Regency and (2) formulate strategies for the development of the tourism potential of Baburai Waterfall in Padang Pariaman Regency. This research uses a qualitative type with a descriptive approach to detail and interpret the data. The results of the research conducted through field observation, interviews, and questionnaires found that there is a lack of good coordination among managers, local government, and tourism departments, leading to limited accessibility to the waterfall, a lack of human resource development, and insufficient promotion regarding the Baburai Waterfall tourist attraction. The analytical technique used is the SWOT method to determine the sustainable development strategy for Kulukubuk waterfall tourism. Based on the results of the SWOT analysis, it is concluded that the development strategy for the Baburai waterfall tourism potential includes building cooperation with the government and the tourism office, improving accessibility, and enhancing the human resources of the Baburai waterfall tourism managers.